دراسة تأثير بعض العوامل البيئية على المحتوى الفينولي لنبات البقص Rhus cotinus L. (منطقة جبلة) - علي, محمد; سلامة, ريم; حميدوش, ديانا (Latakia University Journal -Biological Sciences Series, 2018)
تناولت هذه الدراسة تأثير بعض العوامل البيئية على المحتوى الفينولي لنبات البقص Rhus cotinus L.. جُمعت العينات النباتية (الأوراق، الأزهار واللحاء) من ثلاثة معارض (جنوب، غرب وشمال) على أربعة ارتفاعات (0-300،300-600،600+900،˂900م) في ريف جبلة خلال عام 2016. تم استخلاص العينات الطازجة باستخدام الايتانول 95% كسائل استخلاصي، ثم معايرة المحتوى الكلي من المركّبات الفينولية بتطبيق طريقة الفولين سيكالتو، معبراً عن النتيجة بـ (mg Gallic acid/g fw) باستخدام جهاز مقياس الطيف الضوئي (Spectrophotometer). أظهرت النتائج تفوق الأوراق على الأزهار واللحاء بمحتوها من المركّبات الفينولية، كذلك سجل المعرض الجنوبي القيم الأعلى للمحتوى الفينولي لكل من الأوراق (17.82±0.81ملغ/غ)، الأزهار (17.45±0.81ملغ/غ) واللحاء (17±0.68 ملغ/غ) يليه المعرض الغربي (17.56±0.73،17.07±0.57 ،16.32±0.53ملغ/غ) لكل من الأوراق، الأزهار واللحاء على التوالي، وأخيراً المعرض الشمالي (16.2±1.17 ملغ/غ) للأوراق (15.59±1.68 ملغ/غ) للأزهار و(15.22±0.67 ملغ/غ) للحاء. لُوحظ أيضاً الارتفاع التدريجي للمحتوى الفينولي للأجزاء النباتية للبقص بدءاً من الارتفاع الأول (15.62±1.44ملغ/غ) وصولاً الى الارتفاع الرابع (17.69±0.57 ملغ/غ). أشارت النتائج الى تأثير بعض العوامل البيئية على المحتوى الفينولي لنبات البقص، حيث تفوق المعرض الجنوبي بمحتواه الفينولي على باقي المعارض، كذلك وُجد أن الارتفاع الرابع (˃900m) هو الأفضل من حيث غنى الأجزاء النباتية للبقص بالمركّبات الفينولية. لُوحظ باستخدام تحليل ANOVA وجود فروق معنوية في محتوى الأجزاء النباتية (الأوراق، الأزهار، اللحاء) من المركُبات الفينولية بين الارتفاعات الأربعة و المعارض (p<0.05). This study aimed at investigating the effect of some environmental factors on the phenolic contents of the Rhus cotinus L. plant. Plant samples (leaves, flowers and bark) were collected from three aspects (south, west and north) at four altitudes (0-300, 300-600, 600-900, ˃900m) in the countryside of Jableh in 2016. The fresh samples were extracted using 95% ethanol as an extraction solution, then the total contents of the phenolic compounds were determined spectrophotometrically using the Folin-Ciocalteu reagent, expressing the result by (mg gallic acid/1g fw) using a Spectrophotometer. The results showed that leaves were superior to flowers and bark with phenolic compounds, also southern aspects recorded the highest yield of phenolic contents for leaves (17,82±0.81mg/g), flowers (17.45±0.81 mg/g) and bark (17±0.68 mg/g) followed by the Western aspect (17.56±0.73,17.07±0.57,16.32±0.53 mg/g) for leaves, flowers and bark, respectively, and finally the northern aspect (16.2±1.17mg/g) for leaves, (15.59±1.68mg/g) for flowers and (15.22±0.67mg/g) for bark. We also noticed gradual increase in phenolic contents of the plant parts of the Rhus cotinus L. from the first altitude (15.62±1.44mg/g) to the fourth altitude(17.69±0.57mg/g). The results showed the effect of some environmental factors on the phenolic contents of Rhus cotinus L., where the phenolic contents from southern aspect were higher than that of the rest of the aspects, and the fourth altitude (˃900m) was found to be the best in terms of the richness of the plant parts for Rhus cotinus L. with phenolic compounds. ANOVA analysis showed significant differences in the content of plant parts (leaves, flowers, bark) of phenolic compounds between the four altitudes and aspects (p<0.05).